Towards a politics of communion Catholic social teaching in dark times - Rowlands, Anna (T&T Clark, 2022)
"Anna Rowlands offers a guide to the main time periods, key figures, documents and themes of thinking developed as Catholic Social Teaching (CST). A wealth of material has been produced by the Catholic Church during its long history which considers the implications of scripture, doctrine and natural law for the way these elements live together in community - most particularly in the tradition of social encyclicals dating from 1891. Rowlands takes a fresh approach in weaving overviews of the central principles with case studies which relate to contemporary social policy themes, and by considering the increasingly critical questions concerning the role of CST in a pluralist and post-secular context. As such this book offers both an incisive overview of this distinctive body of Catholic political theology and a new and challenging contribution to the debate about the transformative potential of CST in contemporary society"-- Provided by publisher.